Fabrication of transparent quartz roll mold using a roll-to-plate wrapping process for flexible electronics - NamSeok Lee (Elsevier, 2021)
In this study, we numerically simulated the equivalent stress and deformation of a brittle quartz roll with the aim of optimizing its structure and conditions of use in roll-to-plate (R2P) wrapping with a transparent quartz roll. Initially, we analyzed the equivalent stress and contact phenomena between the quartz rolls and the flexible mold by varying the structural parameters of two differently structured quartz rolls to optimize the structure of the R2P system. The results of our analysis enabled us to determine the structure of the R2P system with a polydimethylsiloxane (PDMS) wrapped quartz roll. Further, we analyzed the effects of the thickness of the PDMS cushion and the E-modulus on the stress experienced by the quartz roll and optimized these parameters for the R2P wrapping process. Finally, we applied the optimized quartz roll structure and condition to the actual R2P wrapping process. In addition, we used our wrapped transparent quartz roll mold for the R2R imprint lithography of a micropattern.